Isolation and characterisation of mesenchymal stem cells derived from human placenta tissue - Vellasamy, Shalini; Sandrasaigaran, Pratheep; Vidyadaran, Sharmili; George, Elizabeth; Ramasamy, Rajesh (Baishideng Publishing Group, 2012)
Aim: To explore the feasibility of placenta tissue as a reliable and efficient source for generating mesenchymal stem cells (MSC). Methods: MSC were generated from human placenta tissue by enzymatic digestion and mechanical dissociation. The placenta MSC (PLC-MSC) were characterized for expression of cell surface markers, embryonic stem cell (ECS) gene expression and their differentiation ability into adipocytes and osteocytes. The immunosuppressive properties of PLC-MSC on resting and phytohemagglutinin (PHA) stimulated allogenic T cells were assessed by means of cell proliferation via incorporation of tritium thymidine (3H-TdR). Results: The generated PLC-MSC appeared as spindle-shaped cells, expressed common MSC surface markers and ESC transcriptional factors. They also differentiated into adipogenic and osteogenic lineages when induced. However, continuous cultivation up to passage 15 caused changes in morphological appearance and cellular senescence, although the stem cell nature of their protein expression was unchanged. In terms of their immunosuppressive properties, PLC-MSC were unable to stimulate resting T cell proliferation; they inhibited the PHA stimulated T cells in a dose dependent manner through cell to cell contact. In our study, MSC generated from human placenta exhibited similar mesenchymal cell surface markers; MSC-like gene expression pattern and MSC-like differentiation potential were comparable to other sources of MSC. Conclusion: We suggest that placenta tissues can serve as an alternative source of MSC for future experimental and clinical studies.